Patient Delay in Accessing Breast Cancer Care in a Sub Saharan African Country: Uganda - Galukande, Moses; Mirembe, Florence; Wabinga, Henry (British journal of medicine and medical research, 2014)
To assess patient delay differences between early and late stage breast cancer among women in Uganda. Study Design—A retrospective analytical study. Place and Duration of the Study—A study conducted at a tertiary teaching hospital. Selected patients’ data available for the period between 2008 and 2011 were included in this study. Methodology—We included 201 women with histologically confirmed breast cancer. The variables analysed included age, residence, histological subtype, stage at presentation and time delays. Ethical approval was obtained. Results—The mean age for the early and late presenters was 49 and 46 years respectively (p=0.065). Rural women were more likely to present late. Triple negative breast cancer (TNBC) and HER2+ were the majority cancer subtypes for the late presenters. On average women waited for 29 months before they presented for specialized cancer treatment (median 12 months; range 1-120 months). The duration of symptoms didn’t differ between the two groups (p=0.295) and 75% of early stage presenters, reported at least 6 months after noticing symptoms. Only 9% of the TNBC patients presented under 3 months in comparison to 14 % for HER2+, 33% for Luminal B and 36% for luminal A. Overall 23% (39/168) presented with early stage disease. Conclusion—Delay in seeking appropriate breast cancer care in Uganda was excessive, a sign of a neglected disease. Tumor biology factors seem to play a role in late stage presentation. Research in factors that lead to prolonged delay in accessing care in a resource poor context are needed urgently.
Keywords: Patient delay; breast cancer; late presentation; Uganda